Design, Instruments, and Data Analysis in STEM Integration Research in Elementary Science Education: A Methodological Review - Juddin, Sura; Maharani, Gezti; Dwi Amanah, Prelia (Indonesian Publication Center, 2025)
The integration of the STEM approach in elementary science education has been increasingly investigated; however, the majority of studies continue to focus primarily on learning outcomes. Methodological aspects that play a crucial role in determining research rigor and validity have not received sufficient attention. This article presents a methodological literature review examining research designs, data collection instruments, and data analysis techniques employed in studies on STEM integration at the elementary level. The review analyzes selected articles from reputable national and international journals accessed through relevant academic databases within a specified publication period. The findings indicate that quantitative quasi-experimental designs dominate the field, while qualitative and mixed-methods approaches remain limited. The most commonly used instruments are learning achievement tests and questionnaires, although both demonstrate limitations in capturing learning processes, engineering practices, and the interdisciplinary nature of STEM integration. Data analysis predominantly relies on descriptive and basic inferential statistics. These findings highlight the need for greater methodological diversification, the development of more authentic and context-sensitive instruments, and the application of more comprehensive analytical techniques to enhance the quality and relevance of STEM integration research at the elementary school level.